Kuávsui já peeivičuovâ. 'Sarastus ja päivänvalo' : Inarinsaamen kielen revitalisaatio - Pasanen, Annika (Suomalais-ugrilainen seura ja Helsingin yliopisto, 2015)
The topic of this study is the revitalization of the Inari Saami language, the only Saami language spoken exclusively in Finland. The Inari Saami language became severely endangered in the 1900s, and toward the 1990s its extinction seemed inevitable. Thanks to conscious efforts originating from the community, this grim path of development was reversed. The most important factors for reversing language shift have been the language nest (an Inari Saami immersion program for children under school age), mother tongue medium school instruction and intensive language education for adults. The Inari Saami language association Anarâškielâ servi, founded in 1986, has played the most important role in the revitalization activities. The study investigates the revitalization of the Inari Saami language on the societal and individual levels between 1997 and 2014. The data consists of interviews with members of the language community, observations from Inari Saami-speaking environments, questionnaires sent to members of Anarâškielâ servi, reports from students of the intensive adult language education program and interviews with their language masters, as well as editorials from the Inari Saami-language Anarâš newspaper. The data is analysed primarily in the light of three main concepts: linguistic culture, language ideologies and ideological clarification. In the study, linguistic culture refers to the combination of historical, political, geographical, sociological, demographic and ideological circumstances under which the Inari Saami language has experienced endangerment and subsequent revitalization. The concept of language ideologies encompasses the language-related attitudes, beliefs, principles and choices prevalent in the language community that have facilitated the revitalization of the language. A third decisive phenomenon from the perspective of the outcome of revitalization is manifested in the process of ideological clarification, which refers to facing language ideologies consciously, recognizing the goals and ...